APLIKASI NON DESTRUCTIVE TEST PENETRANT TESTING (NDT-PT) UNTUK ANALISIS HASIL PENGELASAN SMAW 3G BUTT JOINT - Endramawan, Tito; Haris, Emin; Dionisius, Felix; Prinka, Yuliana (Jurnal Teknologi Terapan, 2017)
The purpose of the research are determine acceptance criteria the specimen based on ASME standard. The research used mild steel materials with hardness 220 HVN with sized 30 cm x 20 cm x 1.2 cm then  SMAW welding process position of 3G buttjoint with rooting electrode LB 52U diameter 2.6 mm used current 70 Amper and voltage 380 volt, for Filler used LB 5218 electrode 3.2 mm with current of 80 Amper and voltage of 380 volts. The welding process influenced by many factor which cause failure. The method for inspect result of weld used Non Destructive Test Penetrant Testing (NDT PT) and used ASME standard for acceptance criteria. The test results showed the discontinuity of porosity on the surface of the welded product in specimen 1 is the largest rounded 5 mm at 233 mm distance so that based on the acceptance criteria of AWS standard, the welding result is accepted and the specimen 2 there is discontinuity at 233 mm with the size of 8 mm so that Otherwise rejected. This rejected result can be improved by gouging the discontinuity and then welded.